Community Support for Forest Conservation Policies in the Komodo Subdistrict - Suryawan, I Wayan Koko; Sianipar, Imelda Masni Juniaty; Lee, Chun-Hung (Institut Pertanian Bogor (IPB University), 2025)
This study delves into the critical determinants that influence community support for forest conservation policies within the Komodo District, utilizing a logistic regression analysis to dissect the impact of various socioeconomic and demographic factors on local residents' attitudes toward conservation. A detailed questionnaire was administered to 520 residents to capture perceptions of conservation measures, infrastructure development, and community involvement. Binary logistic regression revealed that the visibility of conservation efforts, including natural landscape protection and eco-friendly infrastructure, significantly influences public support for policies. There was a strong positive correlation between the visibility of conservation actions and community support. This includes visible protection of natural landscapes and eco-friendly infrastructure, which has significantly bolstered public approval. Adaptive business operations and local training initiatives were positively correlated with support for conservation policies, suggesting that economically beneficial conservation strategies are more likely to win public favor. Lower income levels were unexpectedly associated with more significant support for conservation policies, which could indicate a reliance on the benefits derived from conservation efforts. Conversely, younger demographic groups and island residents displayed a lower propensity to support existing policies. By aligning conservation efforts with the community's economic and social priorities, policymakers can ensure broader support and sustainable engagement.